Captain America the ultimate guide to the first avenger - Forbeck, Matthew; Cowsill, Alan; Wallace, Daniel (New York DK Publishing, 2016)
Presents the comic history of Captain America, from his introduction in the 1940s to the current day, and profiles his key villains, allies, sidekicks, and team affiliations
Comic strips
1 2
Keywords: Avengers -- Fictitious characters; Captain America -- Fictitious character -- Juvenile literature; Picture stories